Evaluation of Protective Equipment Used Among Motorbike Riders - Stiles, Roxanne; Benge, Clint; Stiles, P.J.; Dong, Fanglong; Ward, Jeanette; Ablah, Elizabeth; Haan, James M. (Kansas Journal of Medicine, 2019)
Introduction. This study compared outcomes between patientsinjured at a motorbike track, which requires riders to follow safetyequipment guidelines, and those involved in recreational riding wheresafety equipment usage is voluntary.Methods. A retrospective review was conducted of all patients presentingwith motorbike-related injuries at an American College ofSurgeons verified level-I trauma center between January 1, 2009 andDecember 31, 2013. Data collected included demographics, injurydetails, safety equipment use, hospitalization details, and dischargedisposition. Comparisons were made regarding protective equipmentusage.Results. Among the 115 patients admitted, more than half (54.8%, n =63) were injured on a motorbike track, and 45.2% (n = 52) were injuredin a recreational setting. The majority of patients were male (93.9%),Caucasian (97.4%), and between the ages of 18 to 54 (64.4%). Helmetusage was higher among track riders (95.2%, n = 60) than recreationalriders (46.2%, n = 24, p < 0.0001). Comparisons of injury severity andoutcomes between those who wore protective equipment and thosewho did not were not significant.Conclusions. Even though track riders wore protective equipmentmore than recreational riders, there was no difference between thegroups regarding injury severity or hospital outcomes. These resultssuggested that motocross riders should not rely on protective equipmentas the only measure of injury prevention.Kans J Med 2018;11(2):44-47.